Too sane for this world [videorecording (DVD)] - Grandin, Temple (Cinema Libre Studio, 2014)
Explored are the challenges, gifts, and unique perspective of twelve adults on the autism spectrum. Discussed are the many problems facing the autism community, from bullying to marginalization. The difficulties and experiences that have shaped these twelve individuals should serve as an inspiration to anyone who marches to the beat of a different drummer.